COMPUTERISED COLLOCATE PARTICULARS AND DATA OF THE DEPARTMENT - Mrs. A. Mary Theresa; Ms. Tabitha Maria; Ms. Tashita Maria (Galaxy International Interdisciplinary Research Journal, 2022)
The “COMPUTERISED COLLOCATE PARTICULARS AND DATA OF THE DEPARTMENT” focuses on the collection, storage, and organization of the student’s personal data and academic data for reference and future use.And the data stored in the database can be accessed in the website through links.This website is created as a visual display of the department’s staff, student council information, the activities of the department, including to the student’s data. This website contains hyperlinks which connects the data stored in the cloud database to the website and is made available for the viewers to access. In order to create a website that provides the best display features, provides an easy platform to edit, update and manage the website we have used “WORDPRESS” which is a content management system (CMS) that allows one to host and build websites.